PENGARUH PEMBERIAN PAKAN AMPAS TAHU FERMENTASI DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHANIKAN LELE DUMBO (Clarias graiepinus) - Daud Loha Nguru; Maya F. Roman; Nardi Matias Leo; Abdonia W. Finmeta; Nur Aini Bunyani (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
This research was conducted in Oesapa Selatan Village, Kelapa Lima District, Kupang City, East Nusa Tenggara, in November–January 2026. The research aimed to determine the effect of providing fermented tofu dregs with different doses in feed on the growth of African catfish (Clarias gariepinus), and to determine the dose that provided the best growth results. The research method used a Completely Randomized Design (CRD) with four treatments and four replications to obtain 16 experimental units. The treatments given included P0 (100 g of commercial Hi-Pro-Vite feed without fermented tofu dregs), P1 (10 g of fermented tofu dregs), P2 (15 g of fermented tofu dregs), and P3 (20 g of fermented tofu dregs). The parameters observed included weight gain, body length gain, specific growth rate (SGR), and survival rate (SR). Observations were carried out every 10 days for 40 days of maintenance. Data were analyzed using Analysis of Variance (ANOVA), and if significant differences were found, the Least Significant Difference (LSD) test was performed at the 5% level. The results showed that the provision of fermented tofu dregs significantly affected the growth and survival of African catfish. Treatment P2 (15 g fermented tofu dregs) provided the best results, with the highest weight gain, length gain, SGR, and SR compared to other treatments.